Caracterização nutricional de coprodutos de etanol de milho para suínos - Straub, Igor Willian Wrobel (2021)
The brazilian grains availability enables the grains ethanol and coprodutcs large scale production. The grains ethanol coproducts is feed to swine and it’s energy values variation of coproducts could occur with coproducts of brazilian ethanol grain production.. The variability of coproducts chemical composition impact on the better nutritional formulation to swine. The objectives with this study was to determine DE, ME and it digestible coefficients of brazilean ethanol grain coproducts by pigs and it effects on swine blood parameters. Ten castred male swines with same genectic and origin 25,46± 3,5kg, was housed at metabolic cages, with fecal and urine content collect two times and one time per day respectivily. The experimental delineament was causalized blocks by weight within time repeticion. Was used five diets (referênce and four test coproduct diet). Was observed diferences between most of responses. HPDDGS had presented 4.366 Kcal/Kg ME, bigger then DDG, CBS and DDGS which presented 3.305, 2.934, 3.214 Kcal/Kg ME respectively. EE diets contain HPDDGS and CBS coproducts was 4,00 e 3,53% respectively, it was bigger than DDG and DDGS diet of 1,41 e 1,88% respectively. The urea blood levels of pigs feed with HPDDGS diet was bigger then CBS diet, whereas the pigs triglycerids levels feed with CBS diet was bigger then pigs feed with other diets. DE and EM values of HPDDGS was bigger than DDG, CBS and DDGS diets, which had not differed. DCGE and MCGE values of HPDDGS was bigger than DDG and CBS. Diets influenced blood parameters.